Azole Use in Agriculture, Horticulture, and Wood Preservation – Is It Indispensable? - Jørgensen, Lise Nistrup; Heick, Thies Marten (Frontiers in Cellular and Infection Microbiology, 2021)
Plant pathogens cause significant damage to plant products, compromising both quantities and quality. Even though many elements of agricultural practices are an integral part of reducing disease attacks, modern agriculture is still highly reliant on fungicides to guarantee high yields and product quality. The azoles, 14-alpha demethylase inhibitors, have been the fungicide class used most widely to control fungal plant diseases for more than four decades. More than 25 different azoles have been developed for the control of plant diseases in crops and the group has a world market value share of 20-25%. Azoles have proven to provide long-lasting control of many target plant pathogens and are categorized to have moderate risk for developing fungicide resistance. Field performances against many fungal pathogens have correspondingly been stable or only moderately reduced over time. Hence azoles are still, to date, considered the backbone in many control strategies and widely used as solo fungicides or as mixing partners with other fungicide groups, broadening the control spectrum as well as minimizing the overall risk of resistance development. This review describes the historic perspective of azoles, their market shares and importance for production of major crops like cereals, rice, oilseed rape, sugar beet, banana, citrus and soybeans. In addition, information regarding use in amenity grass, in the wood preservation industry and as plant growth regulators are described. At the end of the review azoles are discussed in a wider context including future threats following stricter requirements for registration and potential impact on human health.